PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PDAM TIRTA MOEDAL SEMARANG - Anityo Angga Santoso; Hari Susanta Nugraha; Agung Budiatmo (Universitas Diponegoro, 2013)
Employee productivity due to many factors, including compensation and motivation. Compensation is remuneration for work performed by employees. While the motivation is anything that raises the spirit or the encouragement of work to achieve work satisfaction. The purpose of this study is that to determine the extent of the influence of compensation and motivation for the production of employee productivity in PDAM Tirta Moedal Semarang. The hypothesis that the influence of compensation (X1) and motivation (X2) of the employee productivity (Y). Type of research is explanatory which, the techniques of file collection using questionnaires. Number of respondent a 80 peoples obtained using simple random sampling. File were analyzed qualitatively and quantitavely by using the a test of validity, reliability, simple linear regression, t test and F test with SPSS 16.0 tools. Based on the analysis of SPSS calculation can be explained that there is the influence of motivation on employee productivity, there is influence between compensation and motivation of employees productivity of PDAM Tirta Moedal Semarang. The conclution is that the compensation and motivation affects employee productivity and the level of closeness has a strong relationship . The suggestion are good companies to readjust the salaries, incentives, and overtime pay provided for employees in terms of both the system and the amount of wages, increase employee motivation to pay more attention to such empoyees, more appreciative of the work of employees, and giving spirit through training interesting, encouraging employees to increase productivity for example by providing more frequent training and conduction periodic